2012
DOI: 10.1371/journal.pone.0036899
|View full text |Cite|
|
Sign up to set email alerts
|

Thermodynamics of Aryl-Dihydroxyphenyl-Thiadiazole Binding to Human Hsp90

Abstract: The design of specific inhibitors against the Hsp90 chaperone and other enzyme relies on the detailed and correct understanding of both the thermodynamics of inhibitor binding and the structural features of the protein-inhibitor complex. Here we present a detailed thermodynamic study of binding of aryl-dihydroxyphenyl-thiadiazole inhibitor series to recombinant human Hsp90 alpha isozyme. The inhibitors are highly potent, with the intrinsic Kd approximately equal to 1 nM as determined by isothermal titration ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 52 publications
1
29
0
Order By: Relevance
“…For protein systems, either a decrease in enthalpy decrease or an increase in entropy is beneficial for maintaining stability. Although no direct studies have focused on the thermodynamic mechanism underlying sHSPs’ chaperone activity towards ADH, several studies suggest that stabilization of client proteins by sHSPs is dominated by enthalpic changes [37, 40]. The enthalpy increase of both plain ELPs [41] and ADH when heated indicated that both the phase transition and aggregation are endothermic processes (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…For protein systems, either a decrease in enthalpy decrease or an increase in entropy is beneficial for maintaining stability. Although no direct studies have focused on the thermodynamic mechanism underlying sHSPs’ chaperone activity towards ADH, several studies suggest that stabilization of client proteins by sHSPs is dominated by enthalpic changes [37, 40]. The enthalpy increase of both plain ELPs [41] and ADH when heated indicated that both the phase transition and aggregation are endothermic processes (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…In order to determine the pH dependence of the observed binding enthalpy, experiments were performed at 25 °C in 50 m m phosphate or 50 m m Tris buffer containing 100 m m NaCl at pH 5.5–9.5 with a final DMSO concentration of 1%, equal in the syringe and the cell. Data were integrated, fitted and analyzed as previously described . All experiments were repeated at least twice.…”
Section: Methodsmentioning
confidence: 99%
“…Global strategies combine multiple experiments in global analyses of ITC (gITC) [9,2128] and in global multi-method analysis (GMMA), the combination of ITC data with data from complementary biophysical disciplines [2932,82]. Beyond merely organizing separate complementary experiments into a hierarchical, multi-stage interpretation, global analysis takes full advantage of all possible constraints of the model and the full statistics of the data by simultaneously and directly fitting all experimental data with one explicit global model.…”
Section: Introductionmentioning
confidence: 99%
“…Beyond merely organizing separate complementary experiments into a hierarchical, multi-stage interpretation, global analysis takes full advantage of all possible constraints of the model and the full statistics of the data by simultaneously and directly fitting all experimental data with one explicit global model. Natural applications of gITC analysis are multi-site binding processes of homo- and hetero-oligomerizing macromolecules [911,13,14,15 ( this volume ),23,3337], displacement experiments [22,38,39], and protonation-linked and other linked binding analyses varying temperature to determine heat capacity changes or buffer composition to determine salt or other co-factor linkage [24,26,28]. …”
Section: Introductionmentioning
confidence: 99%